Effect of hydrothermal pretreatment on mercury removal performance of modified biochar prepared from corn straw. (1st May 2023) - Zhang, Tianle; Zhang, Junying; Wei, Shuzhou; Xiong, Zhuo; Xiao, Rihong; Chuai, Xing; Zhao, Yongchun
Graphical abstract: Highlights: Compare mercury removal performance of biochar pretreated by hydrothermal technique and wet impregnation. Mercury removal performance for biochar pretreated by hydrothermal technique reached 90%. Hydrothermal pretreatment enhanced thermolysis reaction intensity of biomass and extended the specific surface area. Hydrothermal pretreatment could promote the construction of oxygen-containing active sites. Abstract: To further widen the specific surface area and enrich functional groups of biochar for improving the mercury removal performance, this paper compared the difference between wet impregnation and hydrothermal pretreatment to preload ferric chloride on active sites construction of biochar surface. Through systematically evaluating the physicochemical properties of biochar modified by various methods, the mechanism of mercury removal was analyzed. The results indicated that the hydrothermal pretreatment at 180 °C could widen the specific surface area of the precursor benefiting for modifiers adsorption and render the apparent activation energy reduced to 34.11 kJ/mol, causing more intense thermolysis reaction during carbonization. In this way, the specific surface of biochar reached to 282.4 m 2 /g and a more abundant porous structure was constructed. Additionally, after hydrothermal pretreatment, the proportion of chemisorbed oxygen and CO bonds on the surface of biochar was significantly promoted, facilitating the formation of HgO. The improvement of both physical structure and chemical properties of biochar together increases the mercury removal efficiency to over 90 % under the N2 atmosphere.